Analysis of Mathematical Communication Skills and Confidence of 10th Grader of SMK in Geometry Material Viewed from Cognitive Style - Putri, Elanda Laksinta; Dwijanto, Dwijanto; Sugiman, Sugiman (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this study were to describe the mathematical communication skills and the confidence of grade X SMK students on Van Hiele model geometry learning based on their cognitive styles. It was a qualitative descriptive research. The subjects were 2 impulsive students and 2 reflective students which were selected with MFFT instrument. The data collection techniques were mathematical communication skills tests (written and orally), interviews, documentation, attitude scale and activity observation sheets. The results showed that both written and orally, reflective students were able to meet 5 indicators of mathematical communication skills, and less meet another indicators. While, impulsive students less meet all of the mathematical communication skills indictors. The impulsive students confidence was in the medium category. In contrary, the reflective students confidence was in the high category.